Case ACCC/C/2008/32 and Non-compliance of the EU with the Aarhus Convention - Pánovics, Attila (Pécs journal of international and European law, 2017)
The importance of wider public participation in shaping environmental policy and the advantages of better access to courts for citizens and their organisations are widely recognized. The Aarhus Convention obliges contracting parties to guarantee the public environmental rights. These rights are essential tools which contribute to strengthen effective environmental protection policies . The present situation in EU law as far as access to justice in environmental matters is rather complex. EU legal instruments in force do not cover fully the implementation of the obligation resulting from Article 9(3) of the Convention. In March 2017, after extensive and detailed consideration of a communication that was submitted by an environmental NGO in 2008, the Compliance Committee of the Aarhus Convention found that the European Union was in non-compliance with the Convention due to the very limited possibilities for citizens and NGOs to have access to justice at EU level and to bring cases before the Court of Justice of the EU. Hopefully, the case before the ACCC against the EU will have important consequences for the Aarhus-conform interpretation of EU law by the Court.